The Problematic Experience of Players' Mutations Between Clubs: Discovering the Social Adaptability Skills Required - Samuel Owiti; Denis Hauw (Frontiers Media S.A., 2021)
Objective: During their career, most players working in professional team sports move from club to club. These transitions are not always completely successful and could highly impact the route of the players' development. However, there is a lack of knowledge on the psychological processes involved when players encounter problems in adapting from one club to another. Thus, it was the aim of this study to identify the most difficult aspects of these transitions, as experienced by team sports players and the psychological skills that contribute to successful outcomes.Design and Method: The present study included twenty professional basketball players (aged between 20 and 36 years old; Mean = 26.05, SD = 4.12), who had played under different coaches (coach range 4-15; Mean = 8.65, SD = 2.92), and also played for different clubs (range 3-10; Mean = 5.35, SD = 2.08). They took part in retrospective interviews regarding their embedded experiences during club to club transitions. A situated E-approach was used to identify their problematic experiences, the adaptability skills and how they are applied during club mutations.Results and Conclusions: The identification of problematic experiences revealed seven components in relation to coaching (e.g., obeying orders, reduced play time), three components with teammates (e.g., respect), two components with the club (e.g., lack of support), and three components with family/friends (e.g., geographical constraints). Additionally, results indicated that the adaptability skills used during mutation are related to three groups namely mental skills, learning methods, and interpersonal skills. The results provide coaches, players, sports psychologists, and national sport organizations a set of issues for understanding the challenges players encounter when they move from one club to another.